The effects of task-based learning and mentorship on the perceived surgical competency and clinical education condition of surgical technology students - Hanieh Bahadori; Behzad Imani; Meysam Hosseini Amiri (Kashan University of Medical Sciences, 2022)
Background: It is important to investigate the effectiveness of various educational methods in different cultural, educational, and clinical contexts. Objectives: This study aimed to compare the effects of task-based learning (TBL) and mentorship on clinical perioperative competence and clinical education condition of surgical technology students. Methods: A quasi-experimental study was conducted on 50 undergraduate surgical technology students of Hamadan University of Medical Sciences in 2021. Students were selected by the convenience sampling method and were randomized into one of the two groups of TBL or mentorship. Students completed a Perceived Perioperative Competence Scale-Revised questionnaire and a Clinical Education Conditions questionnaire before and after the intervention. Chi-square, independent, and pair samples t-tests were used for data analysis. Results: The pretest mean scores of perceived clinical competence and clinical education condition were, respectively, 106.56 ± 18.34 and 55.56 ± 9.45 in the TBL group and 99.72 ± 16.08 and 53.64 ± 6.89 in mentorship group. No significant difference was found between the two groups in mean overall clinical competence and mean clinical education condition (P > 0.05). After the intervention, the mean scores for perceived clinical competence and clinical education condition increased significantly to 128.92 ± 12.49 and 69.80 ± 6.38 in the TBL group (P < 0.001) and 120.24 ± 16.75 and 69.04 ± 7.23 in the mentorship group (P < 0.001). The posttest mean score of perceived clinical competence was significantly greater in the TBL group than in the mentorship group (P < 0.001). Conclusions: Both the TBL and mentorship methods are effective in improving the clinical competence and clinical education condition of undergraduate surgical technology students.